The role of stroma on normal, hyperplastic and neoplastic prostatic growth, with emphasis on prostatic glycosaminoglycans - De Klerk, Daniel P (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Med.) - University of Stellenbosch, 1984.